STUDY OF CLEAN WATER DISTRIBUTION SERVICES FROM BAHSIKAM SPRINGS IN PDAM TIRTAULI, PEMATANGSIANTAR CITY - Syafaruddin, Shofian; Bahmani-Oskooee, Mohsen; Tony Sohdin Martua Simanjuntak, Edwin; Samosir, Wilson; Delfahedah, Yulia (Universitas Efarina, 2020)
StudyThis study aims to determine the service of distribution of clean water from the Bahsikam spring at PDAM Tirtauli, Pematangsiantar City, especially for the Siantar Marihat sub-district. Where the sample is 100 people. It is known that there is a significant influence between the variables of water color (X1), water odor (X2), water odor (X3) and water pressure (Continuity) on consumer satisfaction (Y) in PDAM Tirtauli, Pematangsiantar City. Based on the table above, the partial test results state that the variable smell of water (X1), taste of water (X2) and color of water (X3) can be seen by comparing the significance value of the variable with α = 5%, so if the significance value is <0.05, the variable is partially independent. significant effect on the independent variable. As for Continuity,The known R Square value is0.993 or 99.3 %indicates that the variable job satisfaction (Y) is affectedthe smell of water (X1), the taste of water (X2) and the color of water (X3),99.3% and the remaining 7% are influenced by variables not examined.in this research.